2022
DOI: 10.15421/142203
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Evolutionary Problem of Filtration Consolidation With the Non-Classical Conjugation Condition

Abstract: Finite-element solutions of the initial-boundary value problem for a nonlinear parabolic equation in an inhomogeneous domain with the conjugation condition of a non-ideal contact were found. The initial boundary value problem is a mathematical model of an important technical problem of filtration consolidation of inhomogeneous soils. Inhomogeneity is considered in terms of the presence of thin inclusions, physicochemical characteristics of which differ from those of the main soil. The problem of longterm conso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…We note that according to known field experiments the filtration, thermoosmotic, and thermal conductivity coefficients depend on porosity n. However, in the consolidation problem, as explained in [20], n = n (h). This is taken into account in the problem (3.1)-(3.10).…”
Section: Mathematical Model Of the Problem In The Domain With A Thin ...mentioning
confidence: 63%
See 2 more Smart Citations
“…We note that according to known field experiments the filtration, thermoosmotic, and thermal conductivity coefficients depend on porosity n. However, in the consolidation problem, as explained in [20], n = n (h). This is taken into account in the problem (3.1)-(3.10).…”
Section: Mathematical Model Of the Problem In The Domain With A Thin ...mentioning
confidence: 63%
“…Suppose that the functions h 0 (x), T 0 (x) are continuous on each of the closures Ω 1 , Ω 2 . Also regarding the coefficients k, k ω , µ, µ ω , λ, λ ω , c s suppose that 1) In the above definition Ψ h , Ψ T are the sets of functions ψ h (x, t), ψ T (x, t), which together with ∂(•) ∂x , are continuous on each of the closures For further explanations, similarly to the work [20], we note the following. Given condition 1), we get…”
Section: A System Of Quasi-linear Equations Of the Parabolic Type Wit...mentioning
confidence: 99%
See 1 more Smart Citation
“…The methodology of deriving these boundary conditions, proposed in this work, allows to take into consideration dependencies of the process parameters along the thickness of the boundary layer. As to the problems with modified conjugation conditions, as described in the proposed methodology, it is demonstrated that significant differences in predictive calculations might arise as compared to the classical conjugation conditions [17,13,10,11]. Our further research will concern numerical experiments and analysis of the influence of these effects on the problems with thin boundary layers.…”
Section: Discussionmentioning
confidence: 99%
“…Here we propose methodology for deriving boundary conditions in the presence of thin boundary layers based on the integral conjugation conditions for geobarriers. Similar modifications for conjugation conditions with nonlinear dependencies are introduced in works [10,11,12,13]. Further, studies [14,15] adjust the conjugation conditions for thin inclusion to consider the effect of biocolmatation according to the methodology of modelling interconnected processes in porous media described in [16].…”
Section: Conjugation Condition For the Heat Transfer With A Thin Laye...mentioning
confidence: 99%